N009 Development of a self-care questionnaire for clinical assessment in patients with inflammatory bowel disease. (16th January 2018) - Lovén Wickman, U; Yngman-Uhlin, P; Hjortswang, H; Wenemark, M; Stjernman, H; Riegel, B; Hollman Frisman, G
Abstract: Background: Patients with inflammatory bowel disease (IBD) have lifelong needs to learn how to manage their symptoms and life situation. The range of actions that patients take in order to manage daily life and maintain health, is defined as self-care. Assessment of self-care may facilitate patient consulting in IBD health care, with the intention to support and strengthen individual efforts to improve their self-care. There is a lack of measures to assess self-care in patients with IBD. The aim of this study was to develop and evaluate the IBD Self-Care questionnaire for assessment of self-care among patients with IBD. Methods: Qualitative and quantitative methods were used to develop the IBD self-care questionnaire. The development and evaluation process was performed in three-phases; (1) item generation based on an interview study on self-care in patients with IBD ( n = 20), (2) content validation assessed with Content Validity Index (CVI) by an expert panel ( n = 6) and patients ( n = 100), ranking and selection of the items, and cognitive interviews to determine the usability of the questionnaire and (3) final evaluation through a pilot study ( n = 93) and a test–retest ( n = 50) after three weeks. An expert review group with three nurses and one physician continuously discussed the result during the development process. Results: A total of 91 patients with Crohn's disease and 102 with ulcerative colitis participated. The final IBD Self-Care questionnaire consisted of 22 items. The assessment of content validity indicated that the items were adequate and easy to understand. Reliability was confirmed with a conformity of 75–100%, in test–retest statistics. Conclusions: An IBD-specific self-care questionnaire was developed with structured methods. The evaluation indicated good validity and reliability. The questionnaire may be a useful tool to assess patients' with IBD ability of self-care in daily practice. However, the results need to be confirmed in further evaluations of larger IBD populations.